High Electron Mobility of Amorphous Red Phosphorus Thin Films. (17th April 2019) - Amaral, Pedro E. M.; Nieman, Glen P.; Schwenk, Gregory R.; Jing, Hao; Zhang, Raymond; Cerkez, Elizabeth B.; Strongin, Daniel; Ji, Hai‐Feng
Abstract: Black phosphorus (BP) has been gathering great attention for its electronic and optoelectronic applications due to its high electron mobility and high I ON/OFF current switching ratio. The limitations of this material include its low synthetic yield and high cost. One alternative to BP is another type of phosphorus allotrope, red phosphorus (RP), which is much more affordable and easier to process. Although RP has been widely used in industry for hundreds of years and considered as an insulating material, in this study, we demonstrate through field‐effect transistors (FET) measurements that amorphous red phosphorus (a‐RP) films are semiconductive with a high mobility of 387 cm 2 V −1 s −1 and a current switching ratio of ≈10 3, which is comparable to the electronic characteristics previously reported for BP. The films were produced via a thermal evaporation method or a facile drop‐casting approach onto Si/SiO2 substrates. We also report a study of the oxidation process of the films over time and a method to stabilize the films via doping a‐RP with metal oxides. The doped films retain stability for one thousand I–V cycles, with no signs of degradation. Abstract : Eine Alternative zu schwarzem Phosphor (BP) ist roter Phosphor (RP), der kostengünstiger und einfacher zu verarbeiten ist. In FET‐Messungen wird gezeigt, dass Schichten aus amorphem rotem Phosphor (a‐RP) halbleitend sind, mit einer hohen Ladungsträgermobilität von 387 cm 2 V −1 s −1 und einem Stromschaltverhältnis von ca. 10 3 ; das ist vergleichbar mit den elektronischen Eigenschaften von BP.